From populism to the "plandemic": why populists believe in COVID-19 conspiracies. (31st May 2021) - Eberl, Jakob-Moritz; Huber, Robert A.; Greussing, Esther
ABSTRACT: Why are COVID-19 conspiracy theories so prevalent? Particularly, why would some citizens ignore scientific evidence and common logic but, instead, be convinced that COVID-19 was a military experiment or spread by 5G signals? Why would they believe that Bill Gates had anything to do with it? In this contribution, we argue that populism is at the centre of these beliefs, as the complex nature of the COVID-19 pandemic makes it an ideal playground for populists' opposition to scientific and political elites. We use Structural Equation Models and panel survey data ( n  = 823) from the Austrian Corona Panel Project to test this argument. We demonstrate a negative correlation of populist attitudes with both trust in political and scientific institutions, which, in return, negatively relate to COVID-19 conspiracy beliefs. This results in an overall positive relationship of populist attitudes and conspiracy beliefs that is independent of political ideology. These findings have important implications for elite communication regarding virus mitigation.